The business of pantomime: regional productions 1865 to 1892 - Sullivan, Jill Alexandra (2005)
Whilst in recent years the study of nineteenth-century popular theatre and culture has expanded into the music hall, fairgrounds and 'minor' theatres, embracing melodrama and spectacle, the Victorian pantomime has attracted little attention. More especially, the widespread and dynamic productions of the English provincial theatres have been largely excluded in discussions that repeatedly focus on the London stage.